P118 LOSS OF SMAD4 EXPRESSION IN ESOPHAGEAL ADENOCARCINOMA (EAC) IS CORRELATED TO POOR SURVIVAL. (23rd November 2019) - Mastracci, L; Isidori, F; Bozzarelli, I; Lugaresi, M; Malvi, D; Hoefnagel, S; Rasanen, J; Soderstrom, H; D'Errico, A; Fiocca, R; Seri, M; Krishnadath, K; et al.
Abstract: Aim: Our study is aimed to evaluate the impact of SMAD4 expression on the clinical outcome of therapy for esophageal adenocarcinoma (EAC). Background & Methods: Esophageal adenocarcinoma is characterized by a high genetic heterogeneity and a low survival rate, despite the adoption of aggressive therapies. We evaluated the expression of SMAD4, a tumor suppressor gene frequently mutated in cancer. by immunohistochemistry in 67 formalin-embedded (FFPE) EAC surgical specimens (patients were primarily treated with surgical resection-naïve cases), 34 of which were analyzed for SMAD4 gene by Next Generation Sequencing (NGS) with a dedicated target panel. Loss of SMAD4 protein was defined by a complete loss of expression in least 30% of cancer cells. Survival curves were determined using Kaplan–Meier methods. Results: Loss of SMAD4 immunoreactivity was found in 33 out of 67 EAC cases (49.3%). Among a subset of 34 cases assessed in NGS, SMAD4 mutations were found in 3 cases (8.8%), all associated with protein loss. Loss of SMAD4 expression was also found in several cases with no mutations in SMAD4 gene (17/34, 50%). Loss of SMAD4 immunoreactivity was associated with poor overall survival (p=0.013) and higher risk of recurrence (p=0.001). Conclusion: Loss of SMAD4 expression was a recurrent event in EAC, linked with genetic mutations in few cases, whereas in the majority of cases it might be related to epigenetic mechanisms, such as promoter hypermethylation. SMAD4 loss was strongly associated with recurrence and poor survival in patients, suggesting SMAD4 expression as potential prognostic biomarker in EAC. Further studies are required to develop strategic therapeutic options directly targeting SMAD4 and/or its regulators.